Women with coronary microvascular dysfunction and no obstructive coronary artery disease have reduced exercise capacity. (15th October 2019) - Bechsgaard, Daria Frestad; Hove, Jens Dahlgaard; Suhrs, Hannah Elena; Bové, Kira Bang; Shahriari, Persia; Gustafsson, Ida; Prescott, Eva
Abstract: Background: Both coronary microvascular dysfunction (CMD) and reduced exercise capacity are associated with adverse cardiovascular prognosis. The association between CMD and cardiopulmonary exercise testing (CPET) derived exercise capacity in symptomatic individuals without obstructive coronary artery disease (CAD) is not clear. We investigated whether exercise capacity was reduced in women with angina, CMD and no obstructive CAD compared with sex-matched controls. Furthermore, we assessed the association between CMD and other CPET-derived variables. Methods: All participants underwent transthoracic Doppler echocardiography of the left anterior descending artery with dipyridamole-induced vasodilation and CPET using ergometer cycle with an incremental test protocol. Results: We included 99 women with angina and no obstructive CAD (patients) and 27 asymptomatic women (controls), age (mean ± standard deviation) 61 ± 10 and 58 ± 10 years, respectively. Patients had a higher burden of risk factors compared with controls, while the weekly physical activity level was comparable between the groups ( p  = 0.72). CMD was present in 27 (27%) patients and 5 (19%) controls. Peak VO2 was significantly reduced in patients with CMD compared with controls with normal coronary microvascular function ((median (IQR) 17.3 (15.5–21.3) vs. 27.3 (21.6–30.8) ml/kg/min; age-adjusted p  = 0.001), independent of cardiovascular risk factors ( p  = 0.041). Presence of CMD in symptomatic women was also associated with diminished heart rate reserve ( p  < 0.001) and blunted heart rate recovery. Conclusions: Women with angina, CMD and no obstructive CAD have markedly reduced exercise capacity compared with sex-matched controls. Moreover, combination of angina and CMD is associated with impaired heart rate response and heart rate recovery. Highlights: Women with angina and no obstructive coronary artery disease have reduced exercise capacity compared with controls Exercise capacity is particularly reduced in women with coronary microvascular dysfunction Presence of coronary microvascular dysfunction is associated with impaired heart rate response and heart rate recovery